Microbial Composition in association with Cayenne Pepper (Capsicum frutescens) Freshness and The Level of Spiciness During Storage at Room Temperature - Hongi, Hasna Nurul Ain; Ijong, Frans G.; Mamuaja, Christine F. (Pascasarjana Unsrat, 2015)
The purpose of this study was to analyze the composition of microbes in total microbial aspects and types of microbes are associated with the level of spiciness and freshness cayenne (Capsicum frutescens) during storage at room temperature. The method is descriptive comparative, results of data derived from a series of laboratory analysis results for test samples covering physical and chemical analysis (moisture content test, pH, Scoville Heat Unit (SHU)), physiological test, and microbiological test (total microbes, isolation, and identification test isolates). Based on the results obtained, it can be concluded: The physical properties of the moisture content and chemical properties pH, decreased corresponding decrease in the level of freshness. Fresh chilli pungency level of 1:10.000 SHU, rather fresh chilli pungency level of 1:25.000 SHU and no fresh chilli pungency level of 1:50.000 SHU. Total bacteria and fungus increases with storage time of chilli, and microbes that associate with freshness chilli is bacteria Bacillus, sp and two types of fungi are Rhizopus, sp and Aspergillus, sp. Keywords : cayenne pepper freshness, microbial composition, the level of spiciness, room temperature